Current status of biobased and biodegradable food packaging materials: Impact on food quality and effect of innovative processing technologies. Issue 2 (6th February 2021) - Nilsen‐Nygaard, Julie; Fernández, Estefanía Noriega; Radusin, Tanja; Rotabakk, Bjørn Tore; Sarfraz, Jawad; Sharmin, Nusrat; Sivertsvik, Morten; Sone, Izumi; Pettersen, Marit Kvalvåg
Abstract: Fossil‐based plastic materials are an integral part of modern life. In food packaging, plastics have a highly important function in preserving food quality and safety, ensuring adequate shelf life, and thereby contributing to limiting food waste. Meanwhile, the global stream of plastics into the oceans is increasing exponentially, triggering worldwide concerns for the environment. There is an urgent need to reduce the environmental impacts of packaging waste, a matter raising increasing consumer awareness. Shifting part of the focus toward packaging materials from renewable resources is one promising strategy. This review provides an overview of the status and future of biobased and biodegradable films used for food packaging applications, highlighting the effects on food shelf life and quality. Potentials, limitations, and promising modifications of selected synthetic biopolymers; polylactic acid, polybutylene succinate, and polyhydroxyalkanoate; and natural biopolymers such as cellulose, starch, chitosan, alginate, gelatine, whey, and soy protein are discussed. Further, this review provides insight into the connection between biobased packaging materials and innovative technologies such as high pressure, cold plasma, microwave, ultrasound, and ultraviolet light. The potential for utilizing such technologies to improve biomaterial barrier and mechanical properties as well as to aid in improving overall shelf life for the packaging system by in‐pack processing is elaborated on.